Days Worked and Seasonality Patterns of Work in Eighteenth Century Denmark - Peter Sandholt Jensen; Cristina Victoria Radu; Paul Sharp (European Historical Economics Society (EHES), 2019)
The calculation of the number of days worked per year is crucial for understanding pre-industrial living standards, and yet has presented considerable obstacles due to data scarcity. We present evidence on days worked and seasonality patterns of work using evidence from a large database of micro-level labor market data for eighteenth century rural Denmark. We estimate that workers worked approximately 5.6 days per week when under full employment. Seasonality of work meant, however, that they were unlikely to find employment during the winter, bringing the estimated number of working days per year to 184. This is lower than often assumed in the literature on real wage calculations, but in line with recent evidence for Malmö and London. We find that days worked increased over the eighteenth century, consistent with the idea of an "industrious revolution". We suggest however that this was probably mostly due to economic necessity rather than a consumer revolution, since unskilled and low skilled workers needed to work over 300 days per year to afford a subsistence basket.
Keywords: J22; N33; 330; working year; seasonality patterns; real wages; annual workers; casual workers; Denmark; eighteenth century